Phytosome: Recent Advance Research for Novel Drug Delivery System - Singh, R. P.; Parpani, S.; Narke, R.; Chavan, R. (Asian Journal of Pharmaceutical Research and Development, 2014)
Development of novel drug delivery systems (NDDS) is a new approach for plant extracts and active components. The available approaches for novel herbal formulations like polymeric nanoparticles, nanocapsules, liposomes, phytosomes, nanoemulsions, microsphere, niosomes, planterosomes, cubosomes, transferosomes, and ethosomes has been reported using bioactive and plant extracts. Phytosome is a patented technology that was introduced and developed by a leading herbal drug manufacturer and nutraceuticals. In phytosomes, incorporated the standardized extracts of plant or water soluble phytoconstituents was improved into phospholipids to form a lipid compatible molecular complex. These phytosomes improve the absorption and bioavailability of drug. This novel formulation has remarkable advantages over conventional formulations of plant actives and extracts which includes enhancement of solubility, bioavailability, ability to cross the cell membranes, protection from toxicity, enhancement of stability, sustained delivery, and protection from physical and chemical degradation. The present review summarizes the water soluble phytoconstituents (like flavonoids, tannins, terpenoids, etc.) that are poorly absorbed either due to their large molecular size or due to their poor lipid solubility, resulting of poor bioavailability, methods of preparation, particle size and shape, entrapment efficiency, route of administration, biological activity and applications of novel formulations